Entrepreneurial Leadership, Human Capital, Knowledge Sharing, and Motivation on Innovation Performance and Competitive Advantage in Startups - Apriyanto Apriyanto; Tekni Megaster (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines the influence of entrepreneurial leadership, human capital, knowledge sharing, and motivation on innovation performance and competitive advantage among startups in Indonesia. Using a quantitative approach, data were collected from 200 startup respondents across various industries through a Likert-scale questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to evaluate both direct and indirect relationships. The results demonstrate that entrepreneurial leadership, human capital, knowledge sharing, and motivation each have a positive and significant effect on innovation performance. Furthermore, innovation performance significantly enhances competitive advantage and mediates the effects of the four independent variables on competitiveness. The findings highlight innovation performance as a strategic link that transforms internal organizational capabilities and employee behaviors into sustainable market advantages. The model exhibits strong explanatory power (R² = 0.671 for innovation performance and R² = 0.713 for competitive advantage), indicating high predictive relevance and good model fit. This research contributes theoretically by reinforcing the resource-based and knowledge-based views (RBV and KBV) of organizational competitiveness, and practically by providing strategic insights for Indonesian startups to strengthen their innovation-driven growth and sustainability